Tapered Microchannel for Multi-particles Passive Separation Based on Hydrodynamic Resistance - Ida Laila Ahmad; Mohd Ridzuan Ahmad (Institute of Advanced Engineering and Science, 2017)
Researches on separation of multi-particles utilizing microfluidic have been flourishing in recent years with the aid from advancements in microfabrication design and technology. Generally, separation is beneficial for biomedical application especially involving heterogeneous samples. Due to inherent problems of samples isolation, a simple and efficient separation device is required. Here, we present a passive tapered microchannel for multi-particles separation using hydrodynamic principle. Our emphasis is on the effect of hydrodynamic resistance coupled with tapered microchannel design. In the experiment, successful multi-particles samples separation was observed. The results were further analyzed and were in agreement with the proposed concept. This method opens the route toward robust, low-cost and high-throughput, thus it may holds potential to be integrated as one functional module in micro total analysis system.